Promotion Policies of Social Economy in Argentina: An Approximation from the Knowledge of Experts - Eliana Lijterman (Íconos)
This article seeks to contribute to the reconstruction of the field of discussion about popular economy by analyzing the discourses of experts that led to the foundation of promotion policies of the “popular economy” implemented in Argentina in 2004. One of the local particularities in the process of institutionalization lies in the official agenda which guides and contains contradictory definitions and valorizations of the popular economy and its subject. While its political and cultural potential were being posited, popular economy was being restricted by an agenda that needed salaried work. This work is based on an extensive archival analysis that compiles a heterogeneity of ministerial documents and specialized fieldwork.